Implementation of a Life of Prayer in a Catholic Family Based on the Familiaris Consortio Document 59-62 - Abdi Guna Sitepu; Elbina Sipangkar; Erikson Simbolon (Journal of Education Technology Information Social Sciences and Health, 2024)
The life of prayer within Catholic families is of paramount importance in strengthening spirituality and familial bonds while nurturing faith values. Document Familiaris Consortio No. 59-62 serves as a primary guideline in understanding Catholic family prayer practices. This research explores the implementation of prayer life in St. Agata Sitaretareon Station, Parish of St. Michael Pangururan, utilizing qualitative research methods. The findings indicate that basic prayer practices, devotions, and daily prayers serve as crucial foundations in the spiritual life of Catholic families. Parents play a central role as the primary instigators of prayer, despite facing challenges such as children's indifference. Families actively engage in both liturgical and personal prayers, demonstrating their commitment to deepening their faith and relationship with God. These prayer practices bring about peace, harmony, and gratitude in the daily lives of Catholic families in St. Agata Sitaretareon Station, serving as tangible evidence of lived faith enriching spirituality and strengthening the faith community in the pursuit of spiritual well-being. Thus, the prayer life within Catholic families in St. Agata Sitaretareon Station, Parish of St. Michael Pangururan, has been effectively carried out, with each family member participating in communal prayer in their daily lives.